A teoria do Estado na obra de István Mészáros: breve aproximação - Firmiano, Frederico Daia [UNESP] (Programa de Pós-Graduação em Serviço Social e Curso de Graduação em Serviço Social da Universidade Federal de Santa Catarina, 2024)
In this paper, we aim to analyze the theory of the State in the István Mészáros’ work. We argue that his critique of the State can be glimpsed in statu nasdendi already in his important study of Marx's theory of alienation. Later it receives extensive treatment in his Magnum Opus, Beyond Capital: Towards a Theory of Transition, when he analyzes the conditions of emergence, development and (structural) crisis of the sociometabolic system of capital in contemporaneity. We can say that even before the incomplete and post mortem publication of Beyond Leviathan: Critique of the State Mészáros had already left a powerful contemporary theory of the State. But it is in this work that we find a sophisticated treatment of problems such as the “affirmation of the Law of the Strongest”, the “illegality as an imposition of state formations” and the “withering away of the state”. In this way, we seek to contribute to the debate on the Marxist theory of the State today.

Neste artigo analisamos a teoria do Estado na obra de István Mészáros. Argumentamos que sua crítica do Estado pode ser vislumbrada in statu nascendi já em seu importante estudo sobre a teoria da alienação em Marx, recebendo amplo tratamento em seu Magnum Opus, Para além do capital: rumo a uma teoria da transição, quando de sua análise das condições de emergência, desenvolvimento e crise (estrutural) do sistema sociometabólico do capital na contemporaneidade. Mas se podemos dizer que, antes mesmo da publicação incompleta, e post mortem, de Para além do Leviatã: crítica do Estado, Mészáros já havia legado uma potente teoria contemporânea do Estado, nesta última encontramos um trato sofisticado de problemas que se expressam desde a “afirmação da Lei do mais forte” e da “ilegalidade como imposição das formações estatais” ao “fenecimento do Estado”. Procuramos, com isso, contribuir com o debate em torno da teoria marxista do Estado atualmente.
The theory of the State in the István Mészáros' work: a brief approach
Keywords: Contemporary Marxist theory of the State; Structural crisis of capital; State bankruptcy; Withering away of the state; teoria marxista contemporânea do estado; crise estrutural do capital; estado em falência; fenecimento do estado